Meningkatkan Pengenalan Huruf Hijaiyah Dengan Menggunakan Alat Peraga Edukatif Melalui Media Stik Es Krim Dan Kertas Origami Di TK Bina Edukasi Pekanbaru - Inmaryanto, Inmaryanto; Nikmah, Nikmah; Muetiawati, Dessy (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research is motivated by the lack of children's ability to recognize hijaiyah letters and the low ability of children to recognize hijaiyah letters, distinguish hijaiyah letters and have not been able to pronounce hijaiyah letters correctly. The purpose of this study was to determine the improvement of children's ability to recognize hijaiyah letters with educational props through the media of ice cream sticks and origami paper through the CAR research method (Classroom Action Research). This research was conducted in two cycles and each cycle was conducted in two meetings. In order for this classroom action research to be successful without any obstacles that interfere with the smooth running of the research, the researcher arranges the stages that are passed in classroom action research, namely: 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. The subjects in this study were B2 grade students with 5 female and 9 male students in the first semester of the 2022/2023 academic year in Kindergarten Bina Edukasi, Rejosari Village, Tenayan Raya District, Pekanbaru City.While the object of this research is the use of educational props through the media of ice cream sticks and origami paper to improve the ability to recognize hijaiyah letters in children. The research data were collected through teacher observation techniques and children's activities and documentation. After the data is collected through observation, the data is processed using the percentage formula.The results of this study are an increase in the learning process carried out by the teacher and the child's ability to recognize the concept of numbers. Observation of children's activities also increased, this can be seen from the initial data to cycle II meeting 2. Initial data was 43.21%, Cycle II meeting 2 obtained an average percentage of 85.38%. So that the overall increase in children's activities to recognize hijaiyah letters obtained an average percentage of 42.17%.